2020
DOI: 10.1002/agj2.20467
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the optimal sampling density to characterize spatial heterogeneity of soil carbon stocks in a Karst Region

Abstract: The aim of this study is to investigate the spatial distribution of soil organic C stock and to determine the optimal number of samples required for its determination, in a small karst basin. By taking the soil organic C stock in the Houzhai River Basin, calculated on the basis of a 150 by 150 m grid sampling design as original data and selecting sample sets at five grid scales (300, 450, 600, 750, and 900 m), the optimal number of samples for different sampling distances was obtained, using geographic informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In addition, the selection of samples in the study area also affects the interpolation accuracy. Zhang et al (2021) compared the interpolation accuracy of SOCS in the Karst Region at different sampling distances, and it was concluded that the interpolation accuracy varied with sample distance. When interpolating in flat areas, it is more sensitive to the distribution of sample points than when interpolating in complex terrain (Long et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the selection of samples in the study area also affects the interpolation accuracy. Zhang et al (2021) compared the interpolation accuracy of SOCS in the Karst Region at different sampling distances, and it was concluded that the interpolation accuracy varied with sample distance. When interpolating in flat areas, it is more sensitive to the distribution of sample points than when interpolating in complex terrain (Long et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This differs from the results found by other scholars at different regions and scales. For example, in a small karst-basin scale with an area of 75 km 2 in Guizhou Province, southern China, 357 sample points could better express the spatial variation of 0-20 cm soil organic carbon, equivalent to 4760 sample points collected on an area of 1000 km 2 [26]. In a small undulating hilly area with an area of 184 hm 2 in São Paulo state of southwestern Brazil, collecting one sample point per 3.75 hm 2 and one sample point per 7.2 hm 2 could satisfy the expression of the spatial variability of SOM and clay, which was equivalent to 26,667 samples and 13,889 samples collected on 1000 km 2 , respectively [27].…”
Section: Comparison Of the Rational Sampling Numbers In Different Reg...mentioning
confidence: 99%